2010
DOI: 10.1007/978-3-642-14799-9_18
|View full text |Cite
|
Sign up to set email alerts
|

Success of Government E-Service Delivery: Does Satisfaction Matter?

Abstract: International audienceFor measuring e-government success a well-founded theory is important which can help governments to improve their services and identify how effectively public money is spent. We propose using citizen satisfaction as a measure of egovernment success, as well as explore its relationships with e-government service quality. Three hypotheses have been formulated to test the model. For empirical estimation, the data used in this study was collected form Sweden. An online survey was conducted us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
(44 reference statements)
3
16
0
2
Order By: Relevance
“…A related finding was reported by (Saha et al, 2010) who reported many factor as correlates of e-government success such as efficiency, actual usage and discrepancy. However, none of these factors is relevant to the one identified as correlated to e-payment system in the present study.…”
Section: Level Of Satisfaction Number Of Responses Percentagesupporting
confidence: 66%
See 1 more Smart Citation
“…A related finding was reported by (Saha et al, 2010) who reported many factor as correlates of e-government success such as efficiency, actual usage and discrepancy. However, none of these factors is relevant to the one identified as correlated to e-payment system in the present study.…”
Section: Level Of Satisfaction Number Of Responses Percentagesupporting
confidence: 66%
“…However, none of the factors considered influencing e-payment satisfaction was captured in Khan study. Saha et al (2010) investigated citizen satisfaction as a determinant of e-government success and also explore the relationship of satisfaction with e-government service quality. Analysis of data reveals that 43% of the variance among the factors of e-service quality, and usage is explained by citizen satisfaction.…”
Section: Information Systems and Users' Satisfaction Related Studiesmentioning
confidence: 99%
“…Although the interest in accountability within e-government research has been steadily growing since 2008 (Lourenco et al, 2017), these efforts are inadequate to address the disorders of accountability relationships. The existing literature abounds with studies that address a variety of elements that contribute to success of e-government implementation in various areas of e-government, such as adoption and implementation (Al-Azri et al, 2010; AL-Naimat et al, 2013), intention to use (Hussein et al, 2011); models of e-government (Nabafu and Maiga, 2012); strategies (Gil-García and Pardo, 2005); service delivery and users' satisfaction (Saha et al, 2010); e-participation (Bataineh and Abu-Shanab, 2016); public value (Karunasena and Deng, 2012); net benefits (Scott and Golden, 2009); and assimilation and the business value (Hossain et al, 2011). However, only few studies have focused on the elements that are essential for e-government implementations to be able to enhance the accountability (Ray, 2012) but limited to the technological and process elements that enhance accountability in public services.…”
Section: E-government and Accountabilitymentioning
confidence: 99%
“…A few scholars (Aladwani, 2011;Al-Busaidy and Weerakkody, 2011;Chen et al, 2015;Chu et al, 2004;El-Haddadeh et al, 2010;Gil-Garcia, 2005;Mirchandani et al, 2008;Saha et al, 2010;Zhang and Hsieh, 2010) have explored Critical Success Factors (CSFs) in e-government as summarized in Table 2.…”
Section: Critical Success Factorsmentioning
confidence: 99%